MANAGEMENT MEASURES OF SHRIMP TRAWLING FISHERY IN ARAFURA SEA, INDONESIA: A CHALLENGE - Nurul Af-idati; Sang-Go Lee (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Since there were many evidences on trawling impact to the environment and society, government has banned trawl operations in Indonesian waters except for those in the Arafura Sea. It is not solely acquitted trawl operation in the area without restrain, but it has been put together with the measures taken to exploit the shrimp resources in optimal manner. Those are input controls, output controls and technical measures. This paper examines two major challenges in applying these management measures: declining of shrimp stock and lack of legal enforcement. Come what may the fishing regulations impose in the shrimp trawling, without effective enforcement, the purpose of fisheries management unlikely will be achieved.